Hypothalamic Pomc expression restricted to GABAergic neurons suppresses Npy overexpression and restores food intake in obese mice - Trotta, Milagros (2020)
Objective: Hypothalamic arcuate proopiomelanocortin (Arc-POMC) neurons are involved in different physiological processes such as the regulation of energy balance, glucose homeostasis, and stress-induced analgesia. Since these neurons heterogeneously express different biological markers and project to many hypothalamic and extrahypothalamic areas, it is proposed that Arc-POMC neurons could be classified into different subpopulations having diverse physiological roles. The aim of the present study was to characterize the contribution of the subpopulation of Arc-POMC neurons cosecreting gamma-aminobutyric acid (GABA) neurotransmitter in the control of energy balance. Methods: Arc-Pomc expression restricted to GABAergic-POMC neurons was achieved by crossing a reversible Pomc-deficient mouse line (arcPomc−) with a tamoxifen-inducible Gad2-CreER transgenic line. Pomc expression was rescued in the compound arcPomc−/−:Gad2-CreER female and male mice by tamoxifen treatment at postnatal days 25 (P25) or 60 (P60), and body weight, daily food intake, fasting glycemia, and fasting-induced hyperphagia were measured. POMC recovery was quantified by immunohistochemistry and semiquantitative RT-PCR. Neuropeptide Y (NPY) and GABAergic neurons were identified by in situ hybridization. Arc-POMC neurons projecting to the dorsomedial hypothalamic nucleus (DMH) were studied by stereotactic intracerebral injection of fluorescent retrobeads into the DMH. Results: Tamoxifen treatment of arcPomc−/−:Gad2-CreER mice at P60 resulted in Pomc expression in ∼23–25% of Arc-POMC neurons and ∼15–23% of Pomc mRNA levels, compared to Gad2-CreER control mice. Pomc rescue in GABAergic-POMC neurons at P60 normalized food intake, glycemia, and fasting-induced hyperphagia, while significantly reducing body weight. Energy balance was also improved in arcPomc−/−:Gad2-CreER mice treated with tamoxifen at P25. Distribution analysis of rescued POMC immunoreactive fibers revealed that the DMH is a major target site of GABAergic-POMC neurons. Further, the expression of the orexigenic neuropeptide Y (NPY) in the DMH was increased in arcPomc−/− obese mice but was completely restored after Pomc rescue in arcPomc−/−:Gad2-CreER mice. Finally, we found that ∼75% of Arc-POMC neurons projecting to the DMH are GABAergic. Conclusions: In the present study, we show that the expression of Pomc in the subpopulation of Arc-GABAergic-POMC neurons is sufficient to maintain normal food intake. In addition, we found that DMH-NPY expression is negatively correlated with Pomc expression in GABAergic-POMC neurons, suggesting that food intake may be regulated by an Arc-GABAergic-POMC → DMH-NPY pathway.